THE EFFECT OF COMBINATION PROGRESSIVE MUSCLE RELAXATION AND MUSIC THERAPY ON BLOOD PRESSURE AND PULSE IN PATIENTS WITH PRIMARY HYPERTENSION IN BABATAN RT 07 RW 01 SURABAYA - Mayangsari, Vandarina Dwi; Septianingrum, Yurike; Khamida, Khamida; Umamah, Farida (Nurse and Holistic Care, 2022)
Background: Hypertension is one of the causes of death in the world, which is also called a "silent killer". Hypertension does not cause symptoms in patients, but the incidence of hypertension as much as 90% is the event of primary hypertension. Hypertention that is not handled can be causing stroke, infarction myocardial, kidney failure and enselopathy. Objective: The study purpose aimed to analyse the effect of a combination of progressive muscle relaxation and music therapy on blood pressure and pulse in patients with primary hypertension in Babatan RT 07 RW 01 Surabaya. Methods: This research used Quasi-experiment with the design of a Non-equivalent Control Group Design. The population consists of 38 people with primary hypertension. The samples of 32 respondents with primary hypertension using nonprobability sampling with purposive sampling technique which was then divided into 2 groups, each of 16 respondents. Independent variable was a combination of progressive muscle relaxation and music therapy, while the dependent variables were blood pressure and pulse. The research instrument used a stethoscope, sphygmomanometer, and stopwatch for a pulse, and observation sheets to record the blood pressure and pulse results. Data analysis was using the paired t-test and independent t-test tests. Result: The results showed that there were differences in blood pressure and pulse in the treatment and control groups before and after the intervention of progressive muscle relaxation and music therapy relaxation. Conclusion: The independent T-test analysis results are obtained in systole, diastole, and the pulse value of ρ = 0,000 <α = 0.05, so that H0 is rejected means that there is an effect of a combination of progressive muscle relaxation and music therapy on blood pressure and pulse.